MCL-1 as a molecular switch between myofibroblastic and pro-angiogenic features of breast cancer-associated fibroblasts - Chloé C. Lefebvre; Philippine Giowachini; Jennifer Derrien; Maxime Naour; Isabelle Corre; Laura Thirouard; Elise Douillard; David Chiron; François Guillonneau; Lucas Treps; Mario Campone; Philippe P. Juin; et al. (Cell Death and Disease)
Abstract Breast cancer-associated fibroblasts (bCAFs) comprise inflammatory CAFs (iCAFs), characterized by the secretion of pro-inflammatory cytokines, and myofibroblastic CAFs (myCAFs), distinguished by their high production of extracellular matrix and their immunosuppressive properties. We previously showed that targeting the anti-apoptotic protein MCL-1 in primary culture of bCAF derived directly from human samples reduces their myofibroblastic characteristics. We herein show by single-cell RNA-sequencing analysis of bCAFs that MCL-1 knock down induces a phenotypic shift from wound-myCAF to IL-iCAF, characterized by the upregulation of genes associated with inflammation as well as angiogenesis-related genes. In vitro, genetic and pharmacologic MCL-1 inhibition increases VEGF secretion by bCAFs, enhancing endothelial cell tubulogenesis. In a chicken chorioallantoic membrane (CAM) model in ovo, co-engraftment of breast cancer cells and bCAFs with reduced MCL-1 expression leads to heightened peritumoral vascular density, driven by VEGF. Mechanistically, the pro-angiogenic phenotype revealed by MCL-1 inhibition is dependent on BAX-BAK activity. It results in NF-κB activation, inhibition of which by a IKKβ inhibitor suppresses the transcription of VEGF and pro-inflammatory factors triggered by MCL-1 inhibition in bCAFs. Chemotherapy downregulates MCL-1 in bCAFs via an increase of NOXA, the endogenous MCL-1 inhibitor, promoting a pro-angiogenic and inflammatory phenotype through the NOXA/MCL-1/NF-kB axis. Overall, these findings uncover a novel regulatory function of MCL-1 in determining bCAF subpopulation differentiation and highlight its role in modulating their pro-angiogenic properties, in response to treatment in particular.